2016
DOI: 10.1073/pnas.1521354113
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and dissection of metabolic oscillations in the microaerobic nitric oxide response network ofEscherichia coli

Abstract: The virulence of many pathogens depends upon their ability to cope with immune-generated nitric oxide (NO · ). In Escherichia coli, the major NO · detoxification systems are Hmp, an NO · dioxygenase (NOD), and NorV, an NO · reductase (NOR). It is well established that Hmp is the dominant system under aerobic conditions, whereas NorV dominates anaerobic conditions; however, the quantitative contributions of these systems under the physiologically relevant microaerobic regime remain ill defined. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 71 publications
4
52
0
Order By: Relevance
“…Previously, computational modeling of the E. coli NO• stress network suggested that loss of respiratory activity would eliminate NO• oscillations and that prediction was confirmed experimentally with use of a triple cytochrome terminal oxidase mutant (∆CYT: ∆ cyoA ∆ appB ∆ cydB ::kanR), which cannot respire on O 2 . Experimentally, ∆ arcA and ∆ arcB eliminated NO• oscillations (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Previously, computational modeling of the E. coli NO• stress network suggested that loss of respiratory activity would eliminate NO• oscillations and that prediction was confirmed experimentally with use of a triple cytochrome terminal oxidase mutant (∆CYT: ∆ cyoA ∆ appB ∆ cydB ::kanR), which cannot respire on O 2 . Experimentally, ∆ arcA and ∆ arcB eliminated NO• oscillations (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…A [Cyd] = [Cyd] 0 or 3B [Cyo] = [Cyo] 0 ). This quantitative disagreement has been discussed previously , and attributed to a parsimonious rate expression for translation that is used within the model. In that previous work, we hypothesized that complex translation dynamics during the oscillatory period were not being sufficiently captured by the model.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations